Being watched by others eliminates the effect of emotional arousal on inhibitory control - Yu, Jiaxin; Tseng, Philip; Muggleton, Neil G.; Juan, Chi-Hung (Frontiers in Psychology, 2015)
The psychological effect of being watched by others has been proven a powerful tool in modulating social behaviors (e.g., charitable giving) and altering cognitive performance (e.g., visual search). Here we tested whether such awareness would affect one of the core elements of human cognition: emotional processing and impulse control. Using an emotion stop-signal paradigm, we found that viewing emotionally-arousing erotic images before attempting to inhibit a motor response impaired participants’ inhibition ability, but such an impairing effect was completely eliminated when participants were led to believe that their facial expressions were monitored by a webcam. Furthermore, there was no post-error slowing in any of the conditions, thus these results cannot be explained by a deliberate speed-accuracy tradeoff or other types of conscious shift in strategy. Together, these findings demonstrate that the interaction between emotional arousal and impulse control can be dependent on one’s state of self-consciousness. Furthermore, this study also highlights the effect that the mere presence of the experimenter may have on participants’ cognitive performance, even if it’s via a webcam.